Distinct pathways mediate the sorting of tail-anchored proteins to the plastid outer envelope. - Preetinder K Dhanoa; Lynn G L Richardson; Matthew D Smith; Satinder K Gidda; Matthew P A Henderson; David W Andrews; Robert T Mullen (PLoS ONE, 2010)
Tail-anchored (TA) proteins are a distinct class of membrane proteins that are sorted post-translationally to various organelles and function in a number of important cellular processes, including redox reactions, vesicular trafficking and protein translocation. While the molecular targeting signals and pathways responsible for sorting TA proteins to their correct intracellular destinations in yeasts and mammals have begun to be characterized, relatively little is known about TA protein biogenesis in plant cells, especially for those sorted to the plastid outer envelope.Here we investigated the biogenesis of three plastid TA proteins, including the 33-kDa and 34-kDa GTPases of the translocon at the outer envelope of chloroplasts (Toc33 and Toc34) and a novel 9-kDa protein of unknown function that we define here as an outer envelope TA protein (OEP9). Using a combination of in vivo and in vitro assays we show that OEP9 utilizes a different sorting pathway than that used by Toc33 and Toc34. For instance, while all three TA proteins interact with the cytosolic OEP chaperone/receptor, AKR2A, the plastid targeting information within OEP9 is distinct from that within Toc33 and Toc34. Toc33 and Toc34 also appear to differ from OEP9 in that their insertion is dependent on themselves and the unique lipid composition of the plastid outer envelope. By contrast, the insertion of OEP9 into the plastid outer envelope occurs in a proteinaceous-dependent, but Toc33/34-independent manner and membrane lipids appear to serve primarily to facilitate normal thermodynamic integration of this TA protein.Collectively, the results provide evidence in support of at least two sorting pathways for plastid TA outer envelope proteins and shed light on not only the complex diversity of pathways involved in the targeting and insertion of proteins into plastids, but also the molecular mechanisms that underlie the delivery of TA proteins to their proper intracellular locations in general.